Analysis of Regional Innovation Systems - International Comparative Study - Dobeš, Ondřej (Univerzita Pardubice, 2021)
The aim of the thesis is to analyze regional innovation systems in selected EU countries and then evaluate and compare them using the existing methodology. The first part of the work is focused on explaining the basic concepts, describing regional innovation systems and how to evaluate them. Subsequently, the socio-economic indicators of selected countries and selected regions are described. The last part of the thesis deals with the analysis of regional innovation systems, evaluation and design of recommendations.
Keywords: regionální inovační systémy; inovace; triple helix; spolupráce; regionální politika; regional innovation systems; innovations; triple helix; cooperation; regional policy